Neurotrophic factors in the porcine ovary: Their effects on follicular growth, oocyte maturation, and developmental competence - Kim, Mirae; Hyun, Sang-Hwan (Frontiers in Veterinary Science, 2022)
Pigs are cost-effective industrial animals because they produce a large number of offspring and have shorter rebreeding intervals compared to other animals, such as non-human primates. The reproductive physiology of pigs has been studied over the past several decades. However, there is not enough research on the effects of the neurotrophic factors on the ovarian physiology and development in pigs. As the ovary is a highly innervated organ, various neurotrophic factors during ovarian development can promote the growth of nerve fibers and improve the development of ovarian cells. Thus, investigating the role of neurotrophic factors on ovarian development, and the relationship between neurotrophic factors and porcine female reproduction is worth studying. Here, we focused on the physiological roles of various neurotrophic factors in porcine ovaries. In addition, this review summarized the current status of the studies related to the relationship between neurotrophic factors and porcine ovarian development.